Targeting Fatty Acid Metabolism in the Treatments of Obesity and Disorders of CNS Cellular Energy Balance - Landree, Leslie E.; Kim, Eun-Kyoung; McCullough, Louise D.; Kuhajda, Francis P.; Ronnett, Gabriele V. (Central Nervous System Agents in Medicinal Chemistry, 2006)
The regulation of cellular energy homeostasis within the CNS is crucial not only to neuronal survival, but to the brain's function as an integrator of hormonal and neural inputs that regulate many functions, such as feeding behavior. The sensing and regulation of CNS cellular energy balance is altered in many diseases. Recent studies have suggested that fatty acid metabolism plays a significant role in regulating cellular energy balance in the brain. This hypothesis is supported by observations that the pharmacological manipulation of fatty acid metabolism alters food intake and causes weight loss. Fatty acid levels are determined by fatty acid synthase (FAS), which catalyzes the de novo synthesis of longchain fatty acids that are stored as triglycerides during energy surplus, and carnitine palmitoyltransferase-1 (CPT-1), the rate-limiting enzyme for entry of long-chain acyl-CoA's into the mitochondria for fatty acid oxidation during energy deficit. Most recently, it has been reported that pharmacological manipulation of fatty acid metabolism can also alter cellular energy balance in a stroke model, thus providing neuroprotection. While the physiological contribution of fatty acid metabolism is a hypothesis that awaits further testing, here, we review studies from a number of laboratories investigating fatty acid metabolism as a therapeutic approach for obesity and disorders of CNS energy balance such as stroke.
Keywords: fatty acid metabolism